Opioid analgesic use and patient‐reported pain outcomes after rhinologic surgery. Issue 4 (3rd December 2018) - Riley, Charles A.; Kim, Matthew; Sclafani, Anthony P.; Kallush, Aron; Kjaer, Klaus; Kacker, Ashutosh S.; Tabaee, Abtin
Abstract : Background: Opioid‐based analgesics are routinely prescribed after elective rhinologic surgery. Balancing appropriate pain management while avoiding overprescription necessitates an evidence‐based approach. Methods: Patients undergoing elective rhinologic surgery, including endoscopic sinus surgery (ESS), septoplasty, or ESS with septoplasty, were prospectively enrolled. Patients completed demographic and psychometric questionnaires assessing attitudes toward pain, baseline anxiety, and depression before surgery. Postoperatively, patients documented peak pain levels (0‐100 visual analog scale) and daily prescription and nonprescription medication requirements over a 2‐week period. Results: Of the 42 patients enrolled, 15 underwent ESS, 14 septoplasty, and 13 ESS with septoplasty. Five patients (11.9%) reported a history of chronic pain before surgery. Patients were given a median of 30 opioid pain pills after surgery: acetaminophen with codeine 325/30 mg (10 patients) or oxycodone with acetaminophen 5/325 mg (32 patients). Patients had a median of 27 pills left over at the end of the study period. Median peak pain levels for all procedures were 22 (range, 0‐94) on day 0, 26.5 (range, 0‐86) on day 1, 8.5 (range, 0‐85) on day 3, and 3 (range, 0‐52) on day 7. Median opioid requirements measured in morphine milligram equivalents (MME) over those same days were 6.0, 4.1, 0, and 0, respectively. Conclusion: Postoperative pain after elective rhinologic surgery appears to peak over the first 3 days and decreases rapidly afterward. Most patients require a few doses of opioid analgesics. Opioid requirements and pain levels did not vary based on surgeon, type and extent of surgery, and demographic factors. Judicious prescribing of opioid medication after rhinologic surgery represents a practical opportunity for rhinologists and otolaryngologists to reduce opioid overprescription and abuse.